Is Race Associated with Referral Disparities for Patients with Diabetic Foot Ulcers? - Kyle M. Schweser MD; Mubinah Khaleel DO; Ashwin Garlapaty; Sam Hawkins; James Cook DVM, PhD; Kylee Rucinski PhD, MHA (Foot & Ankle Orthopaedics)
Category: Diabetes; Other Introduction/Purpose: Racial minorities, including African Americans, Indigenous Americans, Asian Americans, Hispanic/Latinos, and Pacific Islanders are more likely to develop Type II diabetes and experience associated microvascular complications. Amputation rates related to diabetes and/or peripheral arterial disease are three times higher for African Americans, suggesting that race, access, and/or mistrust of the medical community may contribute to adverse outcomes for certain minority groups. Determining where the breakdown along the care continuum occurs is fundamental for achieving equitable outcomes among minority groups. This retrospective study was designed to determine 1) the associations of race and living status with rates of referral to specialists for DFU treatment, and 2) the severity of DFU at time of initial presentation. Methods: Patients were identified from the medical record based on a diagnosis related to diabetic foot ulcers made between January 01, 2018, and June 01, 2023, in the family medicine clinic, endocrinology clinic, or emergency department at a Midwest Level 1 Academic Hospital. Referral incidence to specialty orthopaedic foot clinic, severity at onset based on the Wagner ulcer scale, patient demographics, and National Area Deprivation Index (ADI) were analyzed. Results: 597 patients were eligible for inclusion. Patients seen in the Orthopaedic Specialty Clinic (n=98, 16.4%) were significantly younger (56.5 ± 10.9 years vs.61.1 ± 12.5, p< 0.001). Race was not associated with lower referral rates (p = 1) or source of referral (p = 0.68) to specialty clinic. Ulcer severity upon initial presentation did not differ based on race (p=0.318), however, all patients who initially presented to the emergency department (ED) had more severe ulcers (p = 0.016). Patients referred from the ED had lower National ADI scores (p=0.03). No significant differences in referral source or ulcer severity at presentation were seen for sex, rural status, or marital status, suggesting minority patients with diabetic foot ulcers are referred to specialists equally compared to non-minority patients. Conclusion: Patient race was not associated with decreased referral rate to specialty clinic for diabetic foot complications and ulcer severity at initial presentation. Patients with lower socioeconomic status relied on referrals from the ED, as opposed to their Primary Care Providers. Ubiquitous application of these findings may be limited given the breakdown of ethnic groups in the Midwest, and including other regions in a multicenter study would provide further incite.